Comparative Immunological and Histological Study of the Rat’s Brain Infected with Esherichaia Coli - Hussian, Raflaa S.H.; Anmar M.K. Al-Maamori,; Noor Mahmood Naji,; Zahraa M. ALtae,; Zainab Fadhil Jawad AL-Bawi, (American Journal of Biomedicine and Pharmacy, 2026)
Background: Escherichia coli, an extra-intestinal infection, can break the blood-brain barrier (BBB) and cause serious neurological consequences such meningitis. Objectives: This study looks at how E. coli infection affects brain and visual structures in male and female rats, as well as sex variations in immunological responses, including interleukin-4 (IL-4) levels. Materials and Methods: E. coli was obtained from the Al-Hilla River using membrane filtration and injected into the eyes of 20 rats (10 male and 10 female). Results: After one month, the mice were dissected to extract brain and ocular tissues for histological investigation and IL-4 measurement using an ELISA. Hematoxylin and eosin (H&E) staining was employed to assess structural alterations. The study discovered no statistically significant sex-based variations in IL-4 levels or anatomical measures of the brain and eye in control groups. However, infection caused a substantial increase in brain and ocular diameters in both sexes (p = 0.00), most likely due to inflammation and immunological activation. Males had higher mean values for brain (129.62 vs. 117.98) and ocular (57.16 vs. 49.40) measurements in infected groups, but the difference was not statistically significant (p > 0.05). Infected samples showed structural damage, neuronal degeneration, and increased cellular infiltration, which supported the theory of infection-induced neuroinflammation. Conclusion: E. coli infection has a considerable influence on brain and visual tissues in both sexes because of inflammation. While men saw somewhat higher alterations, IL-4 levels did not differ considerably, indicating similar immunological responses. Larger research are required to investigate modest sex-related differences.